Biomechanical assessment of healthy and keratoconic corneas (with/without crosslinking) using dynamic ultrahigh-speed Scheimpflug technology and the relevance of the parameter (A1L−A2L). Issue 4 (5th June 2018) - Fuchsluger, Thomas A; Brettl, Susanne; Geerling, Gerd; Kaisers, Wolfgang; Franko Zeitz, Philipp
Abstract : Aims: To examine corneal biomechanics in healthy and keratoconic eyes, with or without crosslinking obtained by ultrahigh-speed Scheimpflug measurements (Corvis ST). Methods: One hundred and seventeen eyes were studied in three groups: group 1 (n=39) contained keratoconic eyes without crosslinking. Group 2 (CXL; n=28) comprised keratoconic eyes after crosslinking. These were compared with a control group (n=50 matched healthy eyes). In addition, 10 keratoconus patients, before and after CXL treatment, respectively, were examined. Results: The novel parameter A1L–A2L demonstrated highly significant differences between crosslinked corneas and untreated keratoconic or healthy corneas. Velocity during second applanation (A2V) and deformation amplitude (DA) were significantly increased in crosslinked keratoconic eyes both compared with untreated keratoconic eyes and with healthy controls. Radius at highest curvature also was significant among all groups. Inward applanation length (A1L) was significantly increased in controls, whereas outward applanation length (A2L) was significantly reduced in crosslinked keratoconic eyes compared with both other groups. The follow-up analysis revealed statistically significant changes in pachymetry and intraocular pressure and showed tendencies towards significance in applanation times 1 and 2 and in DA. Conclusions: Both A2V and A2L are viable parameters to discriminate healthy from keratoconic but also crosslinked from non-crosslinked keratoconic corneas. The difference of A1L−A2L could reliably discriminate crosslinked from non-crosslinked and healthy corneas. Follow-up examination in a small cohort allows distinction between crosslinked and untreated keratoconus in follow-up examinations. The difference of A1L-A2L could reliably discriminate crosslinked from non-crosslinked and healthy corneas. Measurements of corneal deformation using dynamic ultrahigh-speed Scheimpflug technology are reproducible and provide useful information about keratoconus assessment and biomechanics. Therefore, the Corvis ST seems to provide useful technology to monitor therapeutic success of crosslinking treatment.